Preservation of architectural-decorative plastics of the historical facades of the end XIX – early of the XX century c. Kiev - Сідорова, Олена; Сідорова, Марія-Юлія (Theory and practice of design, 2019)
The work is devoted to the problem of preservation of architectural and decorative plastic facades of the late 19th - early 20th centuries in the city of Kiev. The beauty and originality of the city of Kiev lies not only in the unique picturesque landscape, expressive silhouettes and exquisite sculptures of the architectural monuments, but also in the original architectural and decorative details of the facades of the ordinary background building. These details are an integral part of the urban environment. Portals, doors, balconies, driveways, soles, decorative gypsum inter-window and window sills, column capitals, bas-relief sculpture have a special charm, good irony and carry unique properties of historical, mythological character. During repair and reconstruction, such elements are often lost, leading to the destruction of the special atmosphere of the urban environment. Architectural and decorative details often encode certain symbolic messages - "mantra-amulets", destruction of which leads to voids in the energy fabric of the city. Therefore, identifying such items and preserving them is an extremely important mission. Goal of this article is to find principles of classification of elements of architectural and decorative plastics of facades. That would help to preserve facades historical and artistic character which most often is lost during the reconstruction and repair of buildings.